Does Sled Training with a Load of 10 Kilograms Have an Effect on the Speed of College Student Soccer Players? - Muhamad Ikhsan; I Dewa Made Aryananda Wijaya Kusuma; Imam Syafii; David Agus Prianto; Bayu Agung Pramono; Yanyong Phanpheng (OVS LLC, 2023)
Study purpose. Running speed is an ability soccer players need to build attack and defence. There needs to be more research in football that applies sleds using specific loads to improve the running ability of college student soccer players. This study aims to analyze the effect of sled training with a load of 10 kilograms on the running speed of college student soccer players. Materials and methods. This study uses a quantitative approach with a quasi-experimental design research type, with the research design used being a one-group pretest-posttest design. The sample used in this research was 14 students taken from a population of 95 individuals using random sampling techniques. The study sample used had characteristics of age 18 ± 0.75 years, height 169.42 ± 5.84 cm, weight 58.5 ± 4.21 kg, and BMI 20.44 ± 2.00. Treatment was carried out for six weeks with a frequency of three times a week. The 20-meter sprint speed test was used as an instrument for collecting speed data. The data analysis technique uses a paired samples t-test at a significance level (α) 0.05. The prerequisite test used is the Shapiro-Wilk test. Results. The research showed increased players' running speed obtained from the pretest results of 4.48 ± 0.291 and the post-test results of 4.15 ± 0.266 from the 20-meter sprint test. Conclusions. Based on the results of the paired sample t-test, it can be concluded that there is a significant increase in the running speed of college student soccer players using 10 kg sleds.